2008
DOI: 10.1021/es8004046
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on the Effects of Diesel Particulate Filter and Selective Catalytic Reduction Systems on a Wide Spectrum of Chemical Species Emissions

Abstract: Two methods, diesel particulate filter (DPF) and selective catalytic reduction (SCR) systems,for controlling diesel emissions have become widely used, either independently or together, for meeting increasingly stringent emissions regulations worldwide. Each of these systems is designed for the reduction of primary pollutant emissions including particulate matter (PM) for DPF and nitrogen oxides (NOx) for SCR. However, there have been growing concerns regarding the secondary reactions that these aftertreatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
54
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 22 publications
(32 reference statements)
11
54
1
Order By: Relevance
“…The vehicles with after-treatment significantly reduced particle-phase PAHs by greater than 99%, irrespective of the driving cycles. The consistently highly removal efficiency by the after-treatments has been also reported in many recent studies (Liu et al, 2008;Liu et al, 2010;Khalek et al, 2011), suggesting >90% reduction of the measured PAHs. The vehicles with after-treatment were more efficient in reducing the gas-phase PAHs during cruise and during the UDDS cycle than during idling operation.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The vehicles with after-treatment significantly reduced particle-phase PAHs by greater than 99%, irrespective of the driving cycles. The consistently highly removal efficiency by the after-treatments has been also reported in many recent studies (Liu et al, 2008;Liu et al, 2010;Khalek et al, 2011), suggesting >90% reduction of the measured PAHs. The vehicles with after-treatment were more efficient in reducing the gas-phase PAHs during cruise and during the UDDS cycle than during idling operation.…”
Section: Resultssupporting
confidence: 83%
“…Studies have consistently confirmed the significant reduction of particle-associated PAHs by the DPFs via filtration (Heeb et al, 2008;Liu et al, 2008). It has been postulated that the DPF act as a reactor, forcing an extended exposure of the gaseous pollutants to the trapped soot particles (Heeb et al, 2008) which may change the pathway of gas-to-particle formation of the semivolatile compounds.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…63 The nature of diesel profiles may change as new engine emission control technologies are implemented. 64 Benz[a]anthracene-7, 12-dione has been shown to be a potential particulate tracer for natural gas combustion particles, showing fairly high emissions rates from consumer-owned natural gas-fired home appliances. 65 There is no remarkable difference in the emissions among different kind of coals, but the combustion conditions play a significant role in PAH emission composition and concentration.…”
Section: Polycyclic Compoundsmentioning
confidence: 99%
“…The majority of experiments are performed on chassis dynamometers under predetermined engine load; a heated hose transfers the exhaust from the tailpipe to full flow exhaust dilution tunnels, and therefore, the exhaust gases are collected at low temperature after being mixed and homogenised with the ambient air (with moderate dilution ratios ranging from 6 to 14) in the dilution tunnel, which is connected to a constant volume sampling system (CVS technique) [45,46]. Chassis dynamometers can also be equipped with dilution systems such as critical-flow Venturi dilution tunnels [47], ejection dilutors [48], or rotating disk diluters [49], but undiluted exhaust can also be directly collected through a sampling probe inserted inside the tailpipe, which is a less conventional method [50].…”
Section: Exhaust Sampling and Collection For Pahs Analysismentioning
confidence: 99%